Myanmar’s Seat At ASEAN: A Charter-Based Reassessment - Hla Myet Chell (Realism: Law Review, 2026)
Five years after the February 2021 state of emergency, ASEAN has shifted from an emergency response toward a sustained restriction of Myanmar’s high-level participation whose legal coherence now warrants scrutiny. This article examines the tension between that practice and the legal architecture of the ASEAN Charter. Adopting a normative juridical method and drawing on primary instruments the ASEAN Charter, the Constitutive Act of the African Union, the Treaty on European Union, and the Vienna Convention on the Law of Treaties it asks whether the restriction is Charter-compatible and whether the Five-Point Consensus has sufficient legal character to ground it. Through comparison with the suspension regimes of the African Union and the European Union, the study finds that the restriction operates outside any formal Charter mechanism and that the Five-Point Consensus, as a non-binding political understanding, cannot supply the missing legal authority. It concludes that ASEAN should relocate its approach within the Charter through Article 48 amendment or authentic interpretation and restore functional engagement, since responsible engagement rather than prolonged exclusion is the more legally coherent course.